STRATEGI KEPUTUSAN PEMBELIAN DALAM BELANJA ONLINE MELALUI APLIKASI SHOPEE - Vira Rahmadayanti; Pristiyono Pristiyono; Zulkarnain Nasution (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Shopee's success as a marketplace cannot be separated from the existence of strategies and innovations in the implementation of digital marketing which are applied to website quality, product reviews, and payment methods, resulting in purchase decisions. the population adopted the Maximum Likelihood Estimation (MLE) where the number of research indicators carried out was 17 x 10 = 170, the number of samples in the survey was determined to be 200 respondents with a purposive sampling technique approach which data collection used primary data online via a google form. SmartPLS data analysis method. The results of the research website quality have a significant effect on purchasing decisions, product reviews have no significant effect on purchasing decisions, payment methods have a significant effect on purchasing decisions, website quality has no significant effect on online shopping satisfaction, payment methods have a significant effect on online shopping satisfaction, purchasing decisions significant effect on online shopping satisfaction, site quality has a significant effect on purchasing decisions mediated by online shopping satisfaction, product reviews have no significant effect on purchasing decisions mediated by online shopping satisfaction and payment methods have a significant effect on purchasing decisions mediated by online shopping satisfaction.